Economic Sustainability From Maqasid Al-Shariah Perspective In Ir 4.0 Era - Mohd Noh, Mohd Shahid (Al-Basirah Journal, 2022)
Economic sustainability is a branch from the objective of hifz al-mal under the framework of Maqasid al-Shariah. In macro perspective, it potentially brings maslahah to society on the long run and generates prosperity in human life. This paper clarifies how Islam views the economic sustainability as well as the pillars or main tenets of it. Then, this paper also clarifies the principles for achieving economic development derived from the evidences of Al-Quran and Sunnah which also aligned with the Maqasid al-Shariah. Besides, Sustainable Development Goals (SDGs) as initiated by United Nations also seemed aligned with the Maqasid al-Shariah in in realizing economic sustainability in society. This paper justifies zakat and waqf are the main instruments that proven the effectivity in creating sustainability by having consistent income and well distributed among recipients and beneficiaries for various causes and reasons for economic purposes. This paper also suggests to enhance further research in this particular topic empirically in order to guide industry players to decide or act towards the sustainability.